Women with polycystic ovary syndrome present with altered endometrial expression of stanniocalcin-1. Issue 2 (9th October 2019) - Khatun, Masuma; Arffman, Riikka K; Lavogina, Darja; Kangasniemi, Marika; Laru, Johanna; Ahtikoski, Anne; Lehtonen, Siri; Paulson, Mariana; Hirschberg, Angelica Lindén; Salumets, Andres; Andersson, Leif C; Piltonen, Terhi T
Abstract: Stanniocalcin-1 (STC-1) is a pro-survival factor that protects tissues against stressors, such as hypoxia and inflammation. STC-1 is co-expressed with the endometrial receptivity markers, and recently endometrial STC-1 was reported to be dysregulated in endometriosis, a condition linked with endometrial progesterone resistance and inflammation. These features are also common in the endometrium in women with polycystic ovary syndrome (PCOS), the most common endocrine disorder in women. Given that women with PCOS present with subfertility, pregnancy complications, and increased risk for endometrial cancer, we investigated endometrial STC-1 expression in affected women. Endometrial biopsy samples were obtained from women with PCOS and controls, including samples from overweight/obese women with PCOS before and after a 3-month lifestyle intervention. A total of 98 PCOS and 85 control samples were used in immunohistochemistry, reverse-transcription polymerase chain reaction, or in vitro cell culture. STC-1 expression was analyzed at different cycle phases and in endometrial stromal cells (eSCs) after steroid hormone exposure. The eSCs were also challenged with 8-bromo-cAMP and hypoxia for STC-1 expression. The findings indicate that STC-1 expression is not steroid hormone mediated although secretory-phase STC-1 expression was blunted in PCOS. Lower expression seems to be related to attenuated STC-1 response to stressors in PCOS eSCs, shown as downregulation of protein kinase A activity. The 3-month lifestyle intervention did not restore STC-1 expression in PCOS endometrium. More studies are warranted to further elucidate the mechanisms behind the altered endometrial STC-1 expression and rescue mechanism in the PCOS endometrium. Abstract : Summary sentence Endometrial expression of STC-1 in the secretory phase is blunted in women with PCOS, suggesting impaired protection against stress.